PATH-23. PROGNOSTIC AND RADIOGRAPHIC CORRELATES OF A PROSPECTIVELY COLLECTED MOLECULARLY PROFILED COHORT OF IDH-WILDTYPE ASTROCYTOMAS. (11th November 2019) - Lin, Andrew; Bale, Tejus; Mellinghoff, Ingo; Tabar, Viviane; Schaff, Lauren; Jonathan Yang, T; Young, Robert; Taylor, Barry; Rosenblum, Marc; Jonsson, Philip
Abstract: BACKGROUND: In the molecular era, the relevance of tumor grade for prognostication of IDH-wildtype (WT) astrocytomas has been debated. It has been suggested that lower-grade gliomas with molecular features of glioblastoma, IDH-WT have a similar prognosis to glioblastoma and should be considered for the same clinical trials. METHODS: We integrated prospective clinical sequencing via the FDA-approved genomic sequencing assay MSK-IMPACT from 564 patients with IDH-WT astrocytomas (26 grade II, 71 grade III, and 467 grade IV) with clinical data. RESULTS: Compared to grade III IDH-WT astrocytomas, grade II tumors harbor fewer chromosome 7/10 alterations and EGFR amplifications (p=0.07 and 0.03), but the same frequency of TERT promoter mutation. In contrast, there is no difference in the frequency of these canonical molecular features in grade III versus grade IV IDH-WT disease. Additionally, grade II astrocytomas harbor fewer cell cycle-pathway alterations than grade III tumors (p=6.9e-7). Progression-free (PFS) and overall survival (OS) for grade II astrocytomas were significantly longer than grade III tumors (p=0.02 and p=0.008, respectively), whereas there was no difference in PFS and OS for grade III compared to grade IV tumors. Median PFS for grade II vs. III vs. IV: 19 mo vs. 11 mo vs. 9 mo; median OS: 44 mo vs. 23 mo vs. 23 mo. In lower-grade IDH-WT astrocytomas, gliomatosis is associated with grade II histology (p=0.04), the absence of cell-cycle alterations (p=0.008), and more alterations in the PI3K-AKT pathway (p=0.09). CONCLUSION: Histologic grade has genotypic and phenotypic associations, remains prognostically important in IDH-WT astrocytomas, and should be considered when enrolling patients to clinical trials.